Acute severe ulcerative colitis: using JAK-STAT inhibitors for improved clinical outcomes - Karthikeyan, Shruthi; Ambastha, Chetan; Keyashian, Kian (Frontiers in Gastroenterology, 2024)
Acute Severe Ulcerative Colitis (ASUC) is a well-known and potentially fatal disease state, characterized by symptoms of systemic toxicity including fever, severe anemia, elevated inflammatory markers, and autonomic instability. The life-threatening nature of this condition requires clinicians to make prompt diagnoses and take rapid action, either directing patients towards surgical interventions or medical management. Failure to treat ASUC may lead to toxic dilation of the colon, hemorrhage, or sepsis. Current algorithms suggest the use of intravenous (IV) corticosteroids upon diagnosis, with transition to oral corticosteroids, calcineurin inhibitors or tumor necrosis factor (TNF) inhibitors upon reduction of severe symptoms for candidates deemed to be amenable to medical management. Within these classes, TNF inhibitors such as Infliximab (IFX) have proven to be the most safe, efficacious, and tolerable for patients. While IFX has much data supporting its benefits in achieving short term remission, there are still high rates of long-term need for colectomy and failure to maintain remission. This is due to interactions between the inflamed gastrointestinal tract, the increased metabolic activity seen in ASUC, and intrinsic pharmacodynamic properties of IFX. Certain novel studies suggest that Janus Kinase (JAK-STAT) inhibitors such as Tofacitinib and Upadacitinib are potent agents to salvage clinical remission achieved by IFX, upon its failure. Here we discuss methods to optimize the dosing of IFX to maximize its efficacy, while exploring recent work done on the safety and efficacy of JAK-STAT inhibitors as a salvage therapy, therefore suggesting a novel treatment algorithm to improve clinical outcomes in medically managed ASUC patients.